The ASEAN Economic Community Blueprint: Implementation and Effectiveness Assessment for Philippine Agriculture - Danilo C. Israel; Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2012)
The ASEAN Economic Community (AEC) Blueprint states the plan of ASEAN countries to unify into a single market and production base. A priority focus for integration is enhancement of trade among ASEAN member countries and long-term competitiveness of food and agriculture products produced within ASEAN. Based on key person interviews, this study identifies the specific gaps in the implementation of the blueprint for the case of Philippine agriculture, and makes appropriate recommendations.The widest gaps in AEC blueprint implementation appears to be in cooperation areas related to private sector linkages, agricultural cooperatives, R&D, and technology transfer. For the private sector, a key factor accounting for the gap is preference for own networking and business arrangement. Development of producer cooperatives is at a nascent phase within the country. Considerable progress has been made in GAP, GAHP, GHP, and GMP; in general harmonization is most advanced where foreign markets have imposed stringent standards, i.e., the case of HACCP.The following measures are recommended: First, to re-examine objectives and targets for cooperation with the private sector, agriculture cooperatives, R&D, and technology transfer. Trade standard harmonization is relatively easily justified; however, the collective rationale for cooperation in the other areas need to be better articulated. Second, within trade standard harmonization, a couple of action items are: i) expedite completion of the ASEAN GAqP; and ii) highlight the issue of small producer inclusion. ASEAN-wide mechanisms toward inclusion of small producers hold a long-term potential for uplifting livelihoods of millions of small farmers and fishers in Southeast Asia; however, this cannot follow the same modality as standards certification for large exporting companies. The blueprint objectives for cooperatives, including other types of producer associations, should be re-examined toward more collective approaches to gain approval and certification.
Keywords: 330; Philippines; market integration; trade harmonization; product standards; producer linkages